2016
DOI: 10.15252/emmm.201506055
|View full text |Cite
|
Sign up to set email alerts
|

The dark matter of the cancer genome: aberrations in regulatory elements, untranslated regions, splice sites, non‐coding RNA and synonymous mutations

Abstract: Cancer is a disease of the genome caused by oncogene activation and tumor suppressor gene inhibition. Deep sequencing studies including large consortia such as TCGA and ICGC identified numerous tumor‐specific mutations not only in protein‐coding sequences but also in non‐coding sequences. Although 98% of the genome is not translated into proteins, most studies have neglected the information hidden in this “dark matter” of the genome. Malignancy‐driving mutations can occur in all genetic elements outside the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
178
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 233 publications
(182 citation statements)
references
References 181 publications
(187 reference statements)
1
178
0
3
Order By: Relevance
“…Of note, the VAV1 Δ778-786 mutation involves a unique mechanism that couples genomic disruption of the VAV1 intron 25-exon 26 boundary with a new splicing event triggered by the coordinated loss of an intraexonic splice silencer in exon 26 and the disruption of the canonical AG intron 25-exon 26 splice acceptor site. Somatic mutations involving splicing sites are a common mechanism of tumor suppressor gene inactivation in cancer, where disruption of splicing donor and acceptor site sequences frequently results in intron retention or exon skipping events and expression of aberrant transcripts containing premature stop codons (41). However, missplicing mutations can also result in oncogene activation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the VAV1 Δ778-786 mutation involves a unique mechanism that couples genomic disruption of the VAV1 intron 25-exon 26 boundary with a new splicing event triggered by the coordinated loss of an intraexonic splice silencer in exon 26 and the disruption of the canonical AG intron 25-exon 26 splice acceptor site. Somatic mutations involving splicing sites are a common mechanism of tumor suppressor gene inactivation in cancer, where disruption of splicing donor and acceptor site sequences frequently results in intron retention or exon skipping events and expression of aberrant transcripts containing premature stop codons (41). However, missplicing mutations can also result in oncogene activation.…”
Section: Discussionmentioning
confidence: 99%
“…He also proposed that RNA molecules were related to diseases, including cancer and angiogenesis [32]. During the following 20 years, researchers around the world working in different fields, continued to investigate RNA control of gene expression [33] and its role in cell-to-cell signaling [34]. Today we are aware that extracellular noncoding RNA, such as miRNA and long non-coding RNA (lncRNA) [35,36], are involved in cellular communication, may be involved in childhood development, and are protected from RNases through association with RNA-binding proteins and/or by their encapsulation inside extracellular vesicles [36,37,38].…”
Section: Micro-intro To the Microrna Worldmentioning
confidence: 99%
“…Lastly, the observed synonymous mutations are assumed to be benign, although recent studies have suggested that even synonymous mutations can have functional, consequences [81, 82]. …”
Section: Human Studiesmentioning
confidence: 99%